Pro MongoDB Development - Vohra, Deepak (Apress : Imprint: Apress, 2015)
Pro MongoDB Development discusses all aspects of using MongoDB in web applications. Java, PHP, Ruby, JavaScript are the most commonly used programming/scripting languages and the book discusses accessing MongoDB database with these languages.  A unique book focused on development with MongoDB using Java as well as other programming languages and techniques. Deepak Vohra is a certified Java programmer/developer who has experience in big data and NoSQL programming. MongoDB along with Hadoop and Java are some of today's most important big data and cloud computing technologies.